A Theory of Price Caps on Nonrenewable Resources - Johnson, Simon; Rachel, Lukasz; Wolfram, Catherine (American Economic Review, 2026)
What is the optimal response of a resource exporter when a price cap is imposed on its main export? This paper develops a dynamic framework incorporating stochastic prices, financial frictions, and market power to study this novel tool of statecraft. With the right design, a price cap can incentivize increased extraction, stabilizing prices in the global market. But the stabilizing effects diminish when there is leakage outside the cap. Consequently, weak enforcement of the policy worsens the trade-off faced by the sanctioning policymaker. We provide a systematic approach to setting and enforcing an optimal cap level in these circumstances. (JEL F12, F14, F51, L71, P28, P33, Q35)